Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/mnras/stt1131
|View full text |Cite
|
Sign up to set email alerts
|

Neutron star deformation due to multipolar magnetic fields

Abstract: Certain multi-wavelength observations of neutron stars, such as intermittent radio emissions from rotation-powered pulsars beyond the pair-cascade death line, the pulse profile of the magnetar SGR 1900+14 after its 1998 August 27 giant flare, and X-ray spectral features of PSR J0821−4300 and SGR 0418+5729, suggest that the magnetic fields of non-accreting neutron stars are not purely dipolar and may contain higherorder multipoles. Here, we calculate the ellipticity of a non-barotropic neutron star with (i) a q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 67 publications
4
86
0
Order By: Relevance
“…Multi-wavelength observations of intermittent radio emissions from rotation-powered pulsars beyond the pair-cascade death line, of the pulse profile of the magnetar SGR 1900+14 after its 1998 August 27 giant flare and of the X-ray spectral features of PSR J0821-4300 and SGR 0418+5729, suggest that the magnetic fields of non-accreting neutron stars are not purely dipolar and may contain higher order multipoles (Mastrano et al 2013). Güver et al (2011) analysed upper bound on the spin-down rate and the high signal-to-noise ratio XMM-Newton spectra of the soft gamma-ray repeater SGR 0418+5729.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-wavelength observations of intermittent radio emissions from rotation-powered pulsars beyond the pair-cascade death line, of the pulse profile of the magnetar SGR 1900+14 after its 1998 August 27 giant flare and of the X-ray spectral features of PSR J0821-4300 and SGR 0418+5729, suggest that the magnetic fields of non-accreting neutron stars are not purely dipolar and may contain higher order multipoles (Mastrano et al 2013). Güver et al (2011) analysed upper bound on the spin-down rate and the high signal-to-noise ratio XMM-Newton spectra of the soft gamma-ray repeater SGR 0418+5729.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, models where magnetic strains are responsible for deforming the star and generating the non-zero time varying mass quadrupole (see e.g. Mastrano et al (2013)) might lead to a prediction for the relative phasing of the gravitational wave and pulsar signals, giving a prediction of the value of φgw,0. Secondly, Bildsten (1998) proposed that temperature asymmetries in the star's crust could generate a non-zero mass quadrupole (see also Ushomirsky et al (2000)).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…And if the higher multipole components are much stronger than the dipole then the mass content of the accretion column could be much larger. Recent investigations have shown that higher multipoles can generate large ellipticity and be good candidates for gravitational waves [26].…”
Section: Gravitational Wavesmentioning
confidence: 99%
“…Strong magnetic fields can also distort the star if the magnetic axis is not aligned with the axis of rotation. Indeed the effects of strong higher multi-poles and toroidal components of the magnetic field in generating such non-axisymmetries have recently been investigated [25][26][27]. Other mechanisms for generating asymmetries could be the development of dynamic instabilities in rapidly rotating neutron stars driven by nuclear matter viscosity [28] or through r-mode oscillations (see [23] and references therein).…”
Section: Introductionmentioning
confidence: 99%